The Syncretism of Islam and Minangkabau Customs from the Perspective of History Education: An Analysis of the Makan Bajamba Tradition in Nagari Koto Tangah - Ulfa Shofi Rohmawati; Rozi Aldi; Ayatullah Ayatullah (Tarikhuna: Journal of History and History Education, 2025)
The Makan Bajamba ritual in Nagari Koto Tangah is a unique Minangkabau tradition that blends Islamic values with local customs. This tradition embodies the syncretism of Islamic culture and Minangkabau customs, rooted in the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK). This research aims to analyze how this syncretism is reflected in the practice of Makan Bajamba and to examine its potential as a medium for historical education and the preservation of cultural values. A qualitative-descriptive approach was employed, with data collected through in-depth interviews, participatory observations, and literature review. The findings indicate that Makan Bajamba serves not only as a ritual tradition but also as a medium for transmitting values of togetherness, respect, and harmony between religious teachings and customs. Islamic influences are evident in the prayers and dining etiquette that promote simplicity, while customary values are reflected in the ritual's social structure and symbolic elements, which emphasize communal unity and social hierarchy. This tradition holds relevance for historical education, as it integrates local history learning with moral and cultural values that can be instilled in younger generations. This study concludes that Makan Bajamba is a tangible manifestation of cultural acculturation and serves as a model for local wisdom-based history education. As a cultural heritage, this tradition requires preservation through collaborative efforts involving the community, government, and educational institutions to maintain its values. Additionally, preserving Makan Bajamba contributes to strengthening the Minangkabau cultural identity in the increasingly homogenized context of globalization.